Hak Kepemilikan Tanah oleh Ahli Waris Warga Negara Asing di Indonesia: Tinjauan atas Putusan Mahkamah Agung Nomor 782 PK/Pdt/2016 - Elan Miranda; Phia Irawan Maharani Purba; Fahri Sabriansyah (PT. Saha Kreasi Indonesia, 2025)
This study examines the legal impact of Supreme Court Decision No. 782 PK/Pdt/2016 concerning the inheritance rights of foreign nationals. This issue arises because, fundamentally, foreign national status cannot be a strong reason for them to own land directly. This study uses a normative legal approach and a case study method by analyzing land law regulations, legal documents, and related references in depth. The results show that despite strict restrictions on foreign nationals, the decision still prioritizes legal certainty regarding inheritance rights. Furthermore, consistency in implementing previous court decisions is also crucial to maintaining a sense of justice and legal certainty. The results of this study are expected to support the development of land law in Indonesia and serve as practical guidance for policymakers and legal practitioners.